Development of a real-time loop-mediated isothermal amplification method for monitoring Pseudomonas lurida in raw milk throughout the year of pasture - Zhang, Shufei; Hu, Lianxia; Xue, Yuling; Zhang, Dong; Zhang, Yaoguang; Wang, Shijie (Frontiers in Microbiology, 2023)
The psychrophilic bacterium Pseudomonas lurida (P. lurida) and its thermostable alkaline proteases can seriously damage raw milk quality. In this study, specific primers were designed for P. lurida’s gyrB and aprX genes, and a real-time loop-mediated isothermal amplification (RealAmp) rapid detection method was developed for the early monitoring of P. lurida and its proteases in raw milk. A phylogenetic tree of the gyrB and aprX genes of P. lurida was constructed to analyze the homology of the design sequence of the RealAmp primer. The DNA of 2 strains of P. lurida and 44 strains of non-P. lurida were detected via RealAmp to analyze the specificity of the primer. It was found that aprX-positive proteases were produced by P. lurida-positive strains only when Pseudomonas fluorescens was negative. The dissociation temperatures of gyrB and aprX in the RealAmp-amplified products were approximately 85.0 °C and 90.0 °C, respectively. Moreover, DNA was detected through a 10-fold dilution of P. lurida in a pure bacterial solution and artificially contaminated skimmed milk. The limit of detection of P. lurida DNA copy number in the pure bacterial solution was 8.6 copies/μL and that in the 10% skimmed milk was 5.5 copies/μL. Further, 144 raw milk samples throughout the year from three farms in Hebei province were analyzed using RealAmp. The highest detection rate of P. lurida was 55.56% in the first and third quarters, and that of proteases was 36.11% in the second quarter. The detection rates of P. lurida and its proteases were the highest in samples collected from pasture 2 (52.08% and 45.83%, respectively), and the ability of P. lurida to produce proteases reached 88%. In conclusion, RealAmp established an early and rapid method for the detection of P. lurida and its proteases in raw milk samples, allowing the identification and control of contamination sources in a timely manner to ensure the quality of milk and dairy products.